ANALISIS PREDIKSI KEBANGKRUTAN MENGGUNAKAN MODEL ALTMAN, SPRINGATE, DAN ZMIJEWSKI PADA PERUSAHAAN FARMASI - Putri Ramadhani Siswanto; Safiga Aulia Romadon (Jurnal Manajemen dan Bisnis, 2021)
The purpose of this study is to look at the prediction of a company's bankruptcy using the Altman, Springate, and Zmijewski models. This study uses a quantitative approach with a population of pharmaceutical companies that have IPOs and have complete financial reports starting from 2015-2020. This study determined the purposive sampling method as a sampling technique so that 48 samples were collected which were used for research. The method used in this research is collecting data, calculating ratios, calculating bankruptcy predictions, making bankruptcy prediction tables, determining bankruptcy prediction results, making bankruptcy prediction results tables, calculating accuracy levels, and drawing conclusions. The results show that the Zmijewski Model has the highest accuracy rate, after Altman, then Springate..